STRUKTUR KOMUNITAS IKAN PADA LUBUK LARANGAN DI DESA RANTAU PANDAN KABUPATEN BUNGO, JAMBI - Sari, Diana; Zakaria, Indra Junaidi; Novarino, Wilson (Metamorfosa: Journal of Biological Sciences, 2016)
The objective of this research is analyse variety of fish species in Lubuk Larangan, Rantau Pandan Village. Reseacher take two location for this research. First location has not inhabitant activity. It is Lubuk Larangan Sar (Headwaters). Meanwhile, at the second location is Lubuk Larangan Tepian (Lower Course). It is has inhabitant activity. This research conducted on March - August 2015 at waterworks Rantau Pandan Village, Bungo Regency, especially Jambi Province. The method was used in this research is survey, and used purposive sampling as technic to take sample based on river condition which is different as long as drainage area at Rantau Pandan Village. Fish species variety at Lubuk Larangan, Rantau Pandan Village is focus to the first location, and at the second location is not different (almost similar).
Keywords: species variety, Lubuk Larangan